XIX-wieczna szkoła w XXI stuleciu - Gawrecki, Lechosław (Wydawnictwo Naukowe UAM, 2012)
The author elaborates on the following thesis – the 21st century generation lives in the age of elec-tronic information and technique but learns in school, the organization of which and way (methods) of education as well as students’ treatment date back to the system formed at the end of the 19th century. The influence of the institutions such as church and school is decreasing and the influence of media is increasing, especially of the Internet and mobile phones. According to the author, these are the main causes of teaching and educational difficulties (problems) in contemporary schools. Furthermore, the analysis of characteristics of information society era was presented. This is the era where today’s students will live and work. In the following chapter the author presents his own four proposals of changes in the education labor system – an increase of funds on education; change the teacher’s education and development system and replacing it with more practice-oriented one. Strengthening the position of the principal so he could have a significant influence on efficiency increase of activities of a particular school, creating a pro-innovative lobby in the country that would support changes in education as well as creating the atmosphere of acceptance for those changes. In the final conclusion the author appeals to people involved in teaching and educational practices not to diagnose critically the contemporary school, but to find some ways of changing it.
Nineteenth-century school in the twenty-first century